Trait contributions to fish community assembly emerge from trophic interactions in an individual-based model - Giacomini, Henrique C. [UNESP]; DeAngelis, Donald L.; Trexler, Joel C.; Petrere, Miguel [UNESP] (Elsevier, 2013)
Community ecology seeks to understand and predict the characteristics of communities that can develop under different environmental conditions, but most theory has been built on analytical models that are limited in the diversity of species traits that can be considered simultaneously. We address that limitation with an individual-based model to simulate assembly of fish communities characterized by life history and trophic interactions with multiple physiological tradeoffs as constraints on species performance. Simulation experiments were carried out to evaluate the distribution of 6 life history and 4 feeding traits along gradients of resource productivity and prey accessibility. These experiments revealed that traits differ greatly in importance for species sorting along the gradients. Body growth rate emerged as a key factor distinguishing community types and defining patterns of community stability and coexistence, followed by egg size and maximum body size. Dominance by fast-growing, relatively large, and fecund species occurred more frequently in cases where functional responses were saturated (i.e. high productivity and/or prey accessibility). Such dominance was associated with large biomass fluctuations and priority effects, which prevented richness from increasing with productivity and may have limited selection on secondary traits, such as spawning strategies and relative size at maturation. Our results illustrate that the distribution of species traits and the consequences for community dynamics are intimately linked and strictly dependent on how the benefits and costs of these traits are balanced across different conditions. © 2012 Elsevier B.V.
Keywords: Community dynamics; Environmental gradients; Fish diversity; Life history; Priority effects; Tradeoffs; Environmental gradient; Commerce; Dynamics; Experiments; Fish; Productivity; Ecology; assembly rule; biomass; body size; coexistence; community ecology; dominance; ecological modeling; egg size; environmental conditions; environmental gradient; fish; functional response; growth rate; individual-based model; life history; life history trait; size at maturity; trade-off; trophic interaction